Australia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes the housing prices in Australia. Housing prices in Australia have increased strongly over the past two decades, including by comparison internationally. Thus housing prices are often argued to be overvalued. Many counter-arguments have been put forward for why such measures are flawed. This paper argues that housing prices are moderately stronger than consistent with current economic fundamentals, but less than a comparison to historical or international averages would suggest. International comparisons of price-to-income ratios suggest that Australia is broadly in line with comparator countries, although significant data comparability issues make inference difficult.